Innovative Accounting For Bali Tourism Management And Competitiveness - PUTRI, Ni Made Nadia Adina; JULIANI, Desak Ketut; KUMLASARI, Ni Putu Eprilia; PRADNYANI, Ni Putu Rahayu; PRATIWI, Ni Nyoman Dini (PT Keberlanjutan Strategis Indonesia, 2025)
This study examines the innovative role of accounting systems in building effective and accountable Bali tourism with a qualitative approach to tourism villages and tourism business actors. Modern accounting systems contribute significantly to financial management through improving record-keeping accuracy and anti-fraud mechanisms based on local culture, supporting strategic decision-making with real-time financial data and environmental impact analysis, and increasing the competitiveness of destinations through standardized financial reporting that facilitates access to financing and strengthens the value of local wisdom. The study also highlights the synergy of local regulations with community participatory accounting practices for sustainable financial governance. Temuan offers an accounting-based tourism governance framework that prioritizes transparency, sustainability, and cultural preservation as pillars of Bali's competitiveness in the digital era.